Cutaneous Larva Migrans on the Dorsum of the Foot in a Rural Primary Care Setting: A Case Report from Sintang, West Borneo - Dwiyana, Cynthia Oktora (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2026)
Cutaneous larva migrans (CLM), commonly termed creeping eruption, is a zoonotic dermatosis resulting from the intraepidermal migration of filariform hookworm larvae, predominantly originating from dogs and cats, and is endemic to tropical and subtropical areas characterized by warm, humid, sandy environments. This report delineates the clinical manifestations, predisposing factors, and therapeutic approaches to CLM in a rural primary care context, aiming to enhance prompt identification and appropriate management. A 45-year-old woman presented with intensely pruritic, erythematous, serpiginous papules on the dorsum of her right foot that had progressively extended over a two-week period. She reported frequent barefoot work in agricultural fields and residence in an area with numerous free-roaming dogs and cats. Physical examination revealed multiple linear, winding erythematous tracks on the dorsum pedis dextra, consistent with CLM. The patient was treated with oral albendazole, ethyl chloride spray, and an oral antihistamine, along with counseling on personal and environmental hygiene. Pruritus significantly improved within one week, and the skin lesions resolved completely within two weeks. This case highlights the critical importance of identifying the distinctive clinical features of CLM and implementing prompt treatment, particularly in resource-constrained rural settings, as early diagnosis and appropriate management can result in rapid symptom resolution and avert avoidable complications.